Subsolidus solution and oxide ionic conductivity of Nd-substituted Bismuth Yttria Fluorites - Rahman, N.; Tan, K.B.; Zainal, Z.; Khaw, C.; Chon, M.P. (Universiti Kebangsaan Malaysia, 2015)
Pure phase Bi1.6Y0.4-xNdxO3 solid solution with x = 0.00, 0.10 and 0.20 was successfully synthesised via conventional solid state method at 850°C in 21 h. The materials were refined and fully indexed with space group Fm-3m and lattice parameters, a ranging from 5.5124(1) Å to 5.5289(4) Å. Variation of the lattice parameters of these materials were found in an almost linear correlation with increasing Nd2O3 dopant concentration. Thermal analysis of Bi1.6Y0.4-xNdxO3 solid solution showed no thermal event that associated with any phase transition or weight loss within the studied temperature range of 35 to 900°C. The electrical properties of the samples were investigated by ac impedance analyser, HP4192 at temperature ranging from 25 to 800°C over frequency of 5 Hz to 13 MHz. Bi1.6Y0.3Nd0.1O3 exhibited the highest oxide ion conductivity among the synthesised samples in Bi1.6Y0.4-xNdxO3 solid solution.